Oxygen saturation among newborns in the first 10 hours of life to detect Critical Congenital Heart Disease - Ductus Dependent - Fatchul Wahab; Mahrus Abdul Rahman; Teddy Ontoseno; Risa Etika; Alit Utamayasa; Taufiq Hidayat; Sarmanu Sarmanu (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACT Delay diagnosis of Critical Congenital Heart Disease (CHD) can be associated with sudden clinical deterioration and dangerous cardiovascular conditions. The oxygen saturation screening among newborns in the first 10 hours of life is essential for early detection of critical CHD. This study aims to prove that measuring oxygen saturation among newborns in the first 10 hours of life can detect critical CHD. This study is a diagnostic experimental with consecutive sampling subjects in the infant care unit of Dr. Soetomo Hospital, including all newborns with birth weight ≥ 1500 grams and oxygen saturation at ≥ 1 hour of age below 90%. The measurement of oxygen saturation uses fingertip pulse oximetry in the right hand and foot at the age of 10 hours. A "positive oxygen saturation" is defined as oxygen saturation ≤ 85% or different oxygen saturation ≥ 3%, while a "negative oxygen saturation" is when the oxygen saturation is 85% to 90% or different oxygen saturation is 3%. Echocardiography is performed for the gold standard. From November 2019 to January 2020, 11 newborns underwent an oxygen saturation examination. Five subjects (45.46%) in the category of positive oxygen saturation, echocardiographic showed all Critical CHD (100%). Six subjects (54.54%) with negative oxygen saturation category, echocardiographic results showed two critical CHD (33.34%) and four non-critical CHD (66.66%). Fisher's exact test p < 0.005 (α). The diagnostic oxygen saturation test among newborns at 10 hours of life shows ≤85%, all subject’s echocardiography (100%) shows detection of critical CHD, while saturation 85% to 90% has of 33.3% for detection of critical CHD. The sensitivity and specificity of oxygen saturation for early diagnosis of critical CHD are 100% and 67%, respectively. Keywords: critical congenital heart disease, oxygen saturation, fingertip pulse oximetry, diagnostic tests*Corresponding Author: wfatchul045@gmail.com